Identification of the SARS-CoV-2 Entry Receptor ACE2 as a Direct Target for Transcriptional Repression by Miz1 - Yang, Jing; Perez, Edith A.; Hou, Changchun; Zhang, Pin; Van Scoyk, Michelle; Winn, Robert A.; Rong, Lijun; Liu, Jing (Frontiers in Immunology, 2021)
Multiple lines of evidence have demonstrated that cigarette smoke or Chronic Obstructive Pulmonary Disease upregulates angiotensin-converting enzyme 2, the cellular receptor for the entry of the severe acute respiratory syndrome coronavirus 2, and predisposes individuals to develop severe Coronavirus disease 2019. The reason for this observation is unknown. We recently reported that loss of function of Miz1 in the lung epithelium in mice leads to a spontaneous COPD-like phenotype, associated with upregulation of angiotensin-converting enzyme 2. We also reported that cigarette smoke exposure downregulates Miz1 in lung epithelial cells and in mice, and Miz1 is also downregulated in the lungs from COPD patients. Here, we provide further evidence that Miz1 directly binds to and represses the promoter of angiotensin-converting enzyme 2 in mouse and human lung epithelial cells. Our data provide a potential molecular mechanism for the upregulation of angiotensin-converting enzyme 2 observed in smokers and COPD patients, with implication in severe Coronavirus disease 2019.